2015
DOI: 10.1021/acs.jafc.5b04913
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Nicotinic Acid (Vitamin B3) and N-Propylamine after Myosmine Peroxidation

Abstract: The alkaloid myosmine (3-(1-pyrroline-2-yl)pyridine) is widespread in biological matrixes including foodstuffs and tobacco products. Some in vitro tests in cellular systems showed mutagenic activity for myosmine. Myosmine activation including peroxidation mechanism employs unstable oxazirane intermediates. The formation of minor metabolite 3-hydroxymethyl-pyridine in rat metabolism experiments as well as in in vitro peroxidation assays suggests its further oxidation to nicotinic acid and possible concomitant f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…The existence of 3-pyridinylaldehyde, which has been postulated in earlier studies of MYO peroxidation, has not yet been confirmed. 5 This strongly supports the conclusion that 3-pyridinylmethanol represents the intermediate in vitro as well as in vivo to perform NA synthesis. NA formation with administered MYO in HepG2 cells yields sufficient concentration to meet the demand of NAD + biosynthesis.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…The existence of 3-pyridinylaldehyde, which has been postulated in earlier studies of MYO peroxidation, has not yet been confirmed. 5 This strongly supports the conclusion that 3-pyridinylmethanol represents the intermediate in vitro as well as in vivo to perform NA synthesis. NA formation with administered MYO in HepG2 cells yields sufficient concentration to meet the demand of NAD + biosynthesis.…”
Section: Discussionsupporting
confidence: 79%
“…49 In vitro peroxidation of MYO has been shown to contribute to NA production under abiotic conditions. 3,5 Owing to the presence of reactive oxygen species and other peroxy-containing species in human saliva and blood, MYO reactions may be spontaneous, similar to the abiotic conditions mentioned herein, and may lead to the formation of NA in the absence of enzymatic oxidation.…”
Section: Influence Of Myo On Expression Of Nad + Biosynthetic Enzymesmentioning
confidence: 90%
See 3 more Smart Citations